Sastra Religius Sebagai Sarana Menumbuhkan Pendidikan Karakter Kristiani [Religious Literature as A Means to Cultivate Christian Character Education] - Abednego Tri gumono; Yusak Tanasyah; Gerald Laoh (Diligentia: Journal of Theology and Christian Education, 2022)
Character education is a major aspect in the learning process, even in all human existence. Generally, superior character will support success so that character becomes the key word in life. That is the main role of character so that the national education goal makes this aspect the main goal in addition to the cognitive and psychomotor aspects. The purpose of this study is to describe the role of religious literature, especially poetry, in growing christian characters. It is realized that literary works have a function in building human life, especially in the aspect of character. The integrated education model contains aspects of character in each field of study or subject. Through subjects or courses, character education is realized. One of the fields of science that includes character education is literature, especially religious literature. Religious literature contains dimensions of life values that can foster character education. This scientific article was developed by exploring the literature as study data. Therefore, this paper is qualitative research. This research is expected to contribute to educational efforts in general in developing Christian character education, particularly through religious literature. By having superior character, students will have integrity, morality, character, and actions that are in harmony with the norms prevailing in society and religious values.BAHASA INDONESIA ABSTRACT: Pendidikan karakter merupakan aspek utama dalam proses pembelajaran, bahkan dalam seluruh kehidupan manusia. Karakter yang unggul akan menunjang kesuksesan secara keseluruhan sehingga karakter menjadi kata kunci dalam kehidupan. Itulah peran utama karakter sehingga tujuan pendidikan nasional menjadikan aspek ini sebagai tujuan utama selain aspek kognitif dan psikomotorik. Tujuan dari penelitian ini adalah untuk mendeskripsikan peran sastra religius, khususnya puisi, dalam menumbuhkan karakter kristiani. Disadari bahwa karya sastra memiliki fungsi dalam membangun kehidupan manusia, khususnya dalam aspek karakter. Model pendidikan terpadu memuat aspek karakter dalam setiap bidang studi atau mata pelajaran. Melalui mata pelajaran atau mata kuliah, pendidikan karakter direalisasikan. Salah satu bidang ilmu yang memuat pendidikan karakter adalah sastra, khususnya sastra agama. Sastra religius mengandung dimensi nilai-nilai kehidupan yang dapat menumbuhkan pendidikan karakter. Artikel ilmiah ini dikembangkan dengan melakukan eksplorasi terhadap karya sastra sebagai data kajian. Oleh karena itu, tulisan ini termasuk dalam penelitian kualitatif. Penelitian ini diharapkan dapat memberikan kontribusi bagi upaya pendidikan pada umumnya dalam mengembangkan pendidikan karakter Kristen, khususnya melalui sastra religius. Dengan memiliki karakter yang unggul, peserta didik akan memiliki integritas, moralitas, budi pekerti, dan tindakan yang selaras dengan norma-norma yang berlaku di masyarakat dan nilai-nilai agama.